Effect of Chronic Heat Stress and Long-Term Feed Restriction on Broiler Performance - Abu-Dieyeh, Z.H. M. (International Journal of Poultry Science, 2006)
An experiment was conducted to investigate the effects of long-term feed restriction on alleviating the effects of chronic heat stress on the performance of 4-8-wk old ISA Vedette broiler birds. Environmental temperatures were constant 25, and 35±2oC in controlled environmental rooms and variable-natural temperature ranged between 21 and 30±2oC in an open-sided poultry house. At 4 weeks of age, Daily feed consumption in all experimental rooms was restricted to 75% and 50% of the daily ad libitum consumption recommended in the management guide for this strain. At the end of experiment, a representative sample of 8-wk-old broilers from each treatment was selected and placed randomly in controlled-environmental chambers set at 40±1oC for heat tolerance test. The results showed that, rearing temperature of 35±2oC in closed environment and variable-natural temperature of 21-30 ± 2oC in the open-sided environment had a significant (p< 0.05) negatively effects on broiler performance. Long-term feed restriction to 75% or 50% reduced significantly (p< 0.05) the growth rate and body gain of 4-8-wk old broilers. The body weight gain of birds reared at 35oC and fed 50% of ad libitum was higher than their counterparts reared at constant 25oC or variable-natural temperature (21-3oC). Feed conversion ratio and survivability were significantly (p< 0.05) improved with increasing feed restriction at high ambient temperature of 35±oC. However, feed restriction at lower ambient temperature of 25oC had negative effects on feed conversion ratio. On the other hand, heat tolerance test showed that, feed restriction improved heat tolerance and increased the heat resistance of 8-wk old broilers when exposed to 40oC. Lower mortality rate and lower rate of increase of rectal temperature of feed restricted birds indicated this. From the results of this experiment, it could be concluded that, ambient temperature and long-term feed restriction significantly affect broiler performance. Moreover, long-term feed restriction at high ambient temperature increase heat resistance and improve the heat tolerance of growing broilers, when exposed to heat waves in summer season.